Analysis of Salivary Microbiome and Its Association With Periodontitis in Patients With Obstructive Sleep Apnea - Chen, Yanlong; Chen, Xuehui; Huang, Xin; Duan, Ying; Gao, He; Gao, Xuemei (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives: The study aimed to analyze the periodontal conditions of patients with obstructive sleep apnea (OSA) in relation to salivary microbiome. Materials and Methods: Totally 54 male adults (27 with OSA, 27 controls) completed this cross-sectional study. All participants were monitored by overnight polysomnography (PSG), and underwent full-mouth periodontal examination. Saliva samples were then collected, and the microbial 16S ribosomal RNA gene was extracted and sequenced. The data was analyzed to demonstrate the microbial distribution and the community structures between two groups. Results: Demonstrated by alpha and beta diversity analysis, the OSA group had a lower microbial richness and a lower observed species than the controls. However, there was no statistical difference of the microbial species diversity and evenness between OSA and non-OSA groups. The number of total operational taxonomic units (OTUs) in the OSA group was fewer, and the distribution of microbiome showed that several gram-positive bacteria had higher abundance in the OSA group. As for periodontal pathogens, the relative abundance of the Prevotella was significantly increased in OSA group. No significant difference was observed in the relative abundance of other pathogens at both genus and species levels. Conclusions: The salivary microbial community structure was altered in patients with OSA in the aspects of species richness and trans-habitat diversity, along with Prevotella, a specific periodontal pathogen increasing. These findings might explain the high prevalence of periodontitis in OSA patients.